Respuesta :

Answer:

-3( 5u - 2v -1 ) = -15u + 6v + 3

Step-by-step explanation:

Distributive property:

The distributive property lets you multiply a sum by multiplying each addend separately and then add the products.

A (B +C + D ) = A×B + A×C + A×D

For example 2(x+y)=2x+2y

Given:

-3( 5u - 2v -1 )

To Remove:

Parenthesis

Solution:

Parenthesis = Brackets

By applying Distributive property to the given equation we get

-3( 5u - 2v -1 ) = -3×5u - -3×2v - -3×1

-3( 5u - 2v -1 ) = -15u + 6v +3

∴  -3( 5u - 2v -1 ) = -15u + 6v +3  ............Required answer